2019
DOI: 10.1016/j.celrep.2019.05.030
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Enzyme Adaptive Unit within Bacterial Folate Metabolism

Abstract: SUMMARY Enzyme function and evolution are influenced by the larger context of a metabolic pathway. Deleterious mutations or perturbations in one enzyme can often be compensated by mutations to others. We used comparative genomics and experiments to examine evolutionary interactions with the essential metabolic enzyme dihydrofolate reductase (DHFR). Analyses of synteny and co-occurrence across bacterial species indicate that DHFR is coupled to thymidylate synthase (TYMS) but relatively independent from the rest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 68 publications
(91 reference statements)
1
23
0
Order By: Relevance
“…Perhaps not surprisingly, we found that pathways of adaptation to genetic inactivation of an antibiotic target provide a route to high levels of resistance. Likewise, a recent study also reported that E. coli cells challenged with increasing concentrations of trimethoprim in the presence of thymidine repeatedly evolved high levels of resistance by thyA loss-of-function mutations besides acquisition of commonly observed resistant mutations in DHFR (Schober et al, 2019). Strikingly, mutations in thyA are also known to confer trimethoprim resistance in bacterial clinical isolates of S. aureus (Chatterjee et al, 2008; Kriegeskorte et al, 2014), and H. influenza (Rodríguez-Arce et al, 2017), which emphasizes the need of laboratory studies of microbial adaptation as useful models to tackle serious global threat.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Perhaps not surprisingly, we found that pathways of adaptation to genetic inactivation of an antibiotic target provide a route to high levels of resistance. Likewise, a recent study also reported that E. coli cells challenged with increasing concentrations of trimethoprim in the presence of thymidine repeatedly evolved high levels of resistance by thyA loss-of-function mutations besides acquisition of commonly observed resistant mutations in DHFR (Schober et al, 2019). Strikingly, mutations in thyA are also known to confer trimethoprim resistance in bacterial clinical isolates of S. aureus (Chatterjee et al, 2008; Kriegeskorte et al, 2014), and H. influenza (Rodríguez-Arce et al, 2017), which emphasizes the need of laboratory studies of microbial adaptation as useful models to tackle serious global threat.…”
Section: Discussionmentioning
confidence: 93%
“…The most crucial factor in determining the fate of D27 mutant evolution appears to be the higher accessibility of mutational routes for inactivating thyA that lead to their fixation very early in the evolution experiment. Thymidylate synthase is the only known enzyme in E. coli able to synthetize dTMP de novo from dUMP, and inactivation of thyA inevitably commits the cell to thymine auxothrophy; reversion of DHFR function on the thyA - background is not expected to change this phenotype, as it is known that folA + thyA - strains are thymine-dependent (Bertino and Stacey, 1966; Schober et al, 2019). Competition between DHFR reversion and thyA inactivation thus appears to be decisive in determining the evolutionary solution.…”
Section: Discussionmentioning
confidence: 99%
“…Because DHFR 56 is known to progress through multiple conformational states during catalysis (Boehr, McElheny, 57 Dyson, & Wright, 2006;Sawaya & Kraut, 1997) (Figure S1), we expected the mutational 58 landscape of DHFR to be constrained by the requirement to adopt these different conformations. 59Moreover, prior work had suggested DHFR is impacted by cellular constraints such as protein 60 quality control (Bershtein, Mu, Serohijos, Zhou, & Shakhnovich, 2013) and the build-up of a 61 toxic metabolic intermediate (Schober et al, 2019). We hence expected deep mutational scanning 62 to reveal a highly constrained mutational landscape for DHFR that would contrast with the 63 mutational tolerance observed in other systems.…”
mentioning
confidence: 95%
“…Moreover, prior work had suggested DHFR is impacted by cellular constraints such as protein 60 quality control (Bershtein, Mu, Serohijos, Zhou, & Shakhnovich, 2013) and the build-up of a 61 toxic metabolic intermediate (Schober et al, 2019). We hence expected deep mutational scanning 62 to reveal a highly constrained mutational landscape for DHFR that would contrast with the 63 mutational tolerance observed in other systems.…”
mentioning
confidence: 95%
“…DHFR also acts closely with TYMS-1 to recycle DHF back to THF. Notably, DHFR1 and TYMS1 are intimately linked as bifunctional enzymes in parasites, and copurify in plants, and together represent the rate-limiting enzymes for one carbon metabolism 1517…”
Section: Resultsmentioning
confidence: 99%